How do Specialist Breast Nurses help breast cancer patients at follow-up? - Jiwa, Moyez; Halkett, Georgia; Deas, Kathy; Ward, P.; O'Connor, Moira; O'Driscoll, C.; O'Brien, E.; Wilson, L.; Boyle, S.; Weir, J. (Royal College of Nursing Australia, 2010)
Background. As the proportion of survivors from breast cancer increases it is possible that follow-up care could be delivered wholly by generalists to relieve over subscribed hospital clinics. However, guidelines seldom take into account the nature of interactions between patients and health care professionals involved in hospital-based follow-up. Methods. Consultations between four Specialist Breast Nurses (SBNs) and 21 consecutive women attending a hospital-based breast cancer follow-up clinic in Western Australia were audio recorded and subjected to a thematic analysis. Recording of consultations ceased with saturation of themes. We analysed the data with reference to theoretical frameworks which postulate that social support is a powerful factor in determining positive health outcomes. We also drew on theories focusing on biographical disruption, biographical reinforcement and biographical reinvention. Results. The majority of participants were Australian born, married women in their sixties. The mean duration of the consultations was 19 min (SD = 7.5, min = 8, max = 43.5). A core theme was the established relationship between the woman and her SBN. Overall, the SBNs played an important role in facilitating the transition of patients by supporting the woman in adjustment to a new self-image and bodily functioning. The SBN accompanies each woman through this phase in her life, while supporting a new narrative, promoting her ‘rebirth’ as someone with ideas, concerns and expectations that have altered significantly after the diagnosis of cancer. Five key themes emerged to demonstrate this supportive role: normalising; facilitating access to services; prevention; promoting self-esteem and promoting a proactive approach. Conclusions. Many women with breast cancer claimed a new perspective on what was now possible, acceptable or desirable in a host of life domains. Our data suggest that the follow-up care of cancer patients is more than just dealing with a checklist of symptoms but requires an understanding of the biographical disruption occasioned by a diagnosis of breast cancer.